Nanoparticles decorated with folate based on a site-selective αCD-rotaxanated PEG-b-PCL copolymer for targeted cancer therapy. Issue 23 (27th May 2020) - Dal Poggetto, Giovanni; Troise, Salvatore Simone; Conte, Claudia; Marchetti, Roberta; Moret, Francesca; Iadonisi, Alfonso; Silipo, Alba; Lanzetta, Rosa; Malinconico, Mario; Quaglia, Fabiana; Laurienzo, Paola
Abstract : NPs fabricated from a mixture of PEG- b -PCL and selectively rotaxanated Fol-PEG(αCD)-PCL showed internalisation in KB cells through an active targeting mechanism. Abstract : Nanoparticles (NPs) made up of biodegradable block copolymers offer significant potential in the field of innovative anticancer therapies. However, the accumulation of NPs in tumour cells remains challenging. Surface decoration with targeting ligands recognizing specific receptors that are overexpressed on the cancer cell membrane represents the most common approach, but the effective exposure of the targeting molecule on the NP surface is often limited. An original method to favor the exposure of folate (Fol) as a targeting ligand on the NP surface is reported here. We focused on the introduction in NPs based on a PEG- b -PCL diblock copolymer of Fol-PEG- b -PCL in which the PEG chain is threaded with α-cyclodextrin (αCD). This selectively rotaxanated copolymer (Fol-PEG(αCD)- b -PCL) was prepared from an α, ω-azido-tosyl-PEG(αCD) pseudorotaxane, taking advantage of the different terminal groups of PEG. Fol and the PCL block, which act as caps to prevent αCD dethreading, were covalently linked to PEG with a "one-step" procedure, giving a rotaxanated copolymer with a high yield and a low host coverage (∼9%). The formation of the inclusion complex was confirmed by 2D-DOSY spectroscopy. Rotaxanated copolymers were fully characterized by elemental analysis, FTIR and 1 H NMR spectroscopy, thermal and thermogravimetric analysis, wide angle X-ray diffraction and polarised optical microscopy. Finally, NPs fabricated from a mixture of PEG- b -PCL and Fol-PEG(αCD)- b -PCL showed, as preliminary results, promising internalisation in KB cells and a good active targeting effect.